On the influence of metal impurities on the thermal contraction of a nitrogen arc - Porytskyy, P. V.; Veklich, A.M. (Вопросы атомной науки и техники, 2006)
The influence of metal impurities on the process of contraction (self-constriction) of an arc discharge is considered in
the ambient atmosphere of nitrogen. The calculations are carried out, and it is shown that the degree of constriction of
an arc discharge is determined by both the thermal characteristics of the gaseous medium and the characteristics of
electron-atom collisions. It is revealed that the shape resonance effect under electron-atom collisions has an influence
on a character of the contraction of an arc.